Effect of Ultrasonic Phacoemulsification on the Quality of Life of Patients with Nuclear-Cortical Cataract - N. M. Agarkov; M. M. Yablokov; D. A. Konyaev; E. V. Popova (Oftalʹmologiâ, 2021)
Currently, there are negative trends in the incidence of cataract, which, along with glaucoma, is the most common cause of visual impairment in various countries. Cataract prevalence continues to be high, necessitating the search for new treatment technologies and criteria for assessing the health and quality of life of this population. The purpose: to study the quality of life of patients with cataract against the background of ultrasonic phacoemulsification with implantation of soft intraocular lenses. Nei-VFQ-25 quality of life was studied in 182 patients with nuclear–cortical form of cataract before and after ultrasonic phacoemulsification. The integral index and components of the quality of life of patients with cataract before treatment are significantly reduced. The quality of life of patients with cataracts significantly increases in 3 months after surgical treatment in all indicators. Especially vision significantly improved in the distance, near vision, General health. Improving the quality of life of patients with cataracts after treatment indicates the effectiveness of the used ultrasonic phacoemulsification. In this case, the cause is a violation in the field of role-playing physical and emotional functioning. In the long-term period (6 months after treatment) there is an improvement in the quality of life of patients with mechanical trauma in many respects, except for the role of physical functioning. This study for the first time revealed the effect of ultrasonic phacoemulsification with implantation of soft intraocular lenses on the quality of life of patients with cataract. For the first time using a specific questionnaire NEI-VFQ-25 revealed the scale on which there is an improvement in the quality of life after surgery. The leading indicators of quality of life of patients with cataracts, characterizing the effectiveness of treatment with high-tech method of ultrasonic phacoemulsification, were established for the first time.